Legal Convergence between Banking Law and Commodity Futures Law in the Practice of Bullion Banking - Diana R.W. Napitupulu (Leges Privatae, 2026)
This article examines the legal convergence between banking law and commodity futures law in bullion banking. The financialization of gold has shifted its role from a purely tangible commodity to a dual-function asset that operates as both a tradable commodity and a financial instrument, thereby blurring the regulatory boundaries between prudential banking supervision and commodity futures regulation. Bullion banking includes gold accounts, gold-based financing, custody services, and gold-linked derivatives such as swaps and forwards. These activities resemble traditional banking intermediation when banks accept gold deposits or create claims over gold, while simultaneously mirroring commodity futures trading through derivative contracts. This creates regulatory tension, as banking law prioritizes systemic stability, capital adequacy, and depositor protection, whereas commodity futures law emphasizes market integrity, transparency, and investor protection. Legal convergence is most evident in three areas: unallocated gold accounts functioning like monetary deposits, over-the-counter gold derivatives resembling futures contracts, and custody and clearing mechanisms overlapping with exchange-based infrastructures. In Indonesia’s sectoral regulatory system, where banking and commodity futures oversight are institutionally separated, bullion banking may generate jurisdictional ambiguity, inconsistent risk standards, and opportunities for regulatory arbitrage. The unclear legal classification of gold as property, financial instrument, or contractual claim further complicates ownership, insolvency treatment, and priority rights, ultimately affecting legal certainty and systemic resilience.